Comparison of the effect of LASIK parameters on the percent tissue altered (1‐dimensional metric) versus percent volume altered (3‐dimensional metric). Issue 7 (July 2018) - Gatinel, Damien; Saad, Alain; Binder, Perry S.
Abstract : Purpose : To determine the theoretical volumes of flap and tissue ablation altered during laser in situ keratomileusis (LASIK) correction of myopic refractive errors. Setting : Rothschild Foundation, Paris, France. Design : Experimental study. Methods : The theoretical volumes of the flap and ablated corneal lenticules for spherical myopic corrections were calculated by mathematical approximations based on a simplified geometric model. These results were then compared for various zone diameters, dioptric corrections, and the percentage of the volumes altered (PVA) with the percentage of tissue altered (PTA). Results : The volume of the flap varied linearly with flap thickness and with the square of the flap diameter. The volume of ablated corneal tissue was estimated to be proportional to the magnitude of myopia treatment and to the 4th power of the treatment diameter. For the same depth of ablation, the volume of tissue ablated can vary significantly, depending on the magnitude of the correction and the optical zone diameter. As a result, the PTA calculation is not predictive of the actual PVA. Conclusions : The flap diameters and the laser correction were the most important determinants of the PVA altered during LASIK surgery. New models estimating the volume of the flap and corneal tissue might be necessary to determine their influence on corneal biomechanical stability and each procedure's outcome.